Pengembangan Bahan Ajar Menyimak Berbasis Multimedia Interaktif pada Pelajaran Tematik dengan Tema “Indahnya Kebersamaan” untuk Siswa Kelas IV Sekolah Dasar - Linda Apriati; Widyatmike Gede Mulawarman; Mohammad Ilyas (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to develop thematic teaching materials based on interactive multimedia to improve students' listening skills. This study used the research and development model of Borg and Gall (1983). The multimedia-based thematic teaching materials developed were validated by linguists, media experts and graphic experts. The stages of testing teaching materials consist of small group trials and field trials. The validation of material experts was 87.5%; the results of the validation of linguists were 82.5%; the results of the validation of graphic experts were 87.5%. Based on data and student response questionnaires, learning multimedia-based teaching materials can attract students' interest. Student learning outcomes show a positive status. Thus, the product that can be developed is useful in the learning of fourth-grade elementary school students.